Always together: an extremely long pair bond in rufous horneros - Diniz, Pedro [UNESP] (Springer Nature, 2025)
Prolonged pair bonds, commonly reported in long-lived non-passerines that reunite each breeding season, are often linked to enhanced reproductive performance through improved partner familiarity. However, such bonds are rarely described in year-round territorial birds, particularly those with low sexual conflict. Here, I report a rufous hornero (Furnarius rufus) pair that remained together for at least 10 years within the same urban territory. This surpasses known pair bond durations for passerines (2–7 years) and rivals the time the partners spent together in many non-passerines. Over time, I observed morphological and acoustic changes, with the female showing more signs of senescence (feather deterioration) and the partners tending to exhibit slower duet responses and reduced song synchronization. Conversely, duet-level vocal performance traits, such as minimum frequency, bandwidth, and frequency modulation, tended to improve. As a model of sexual cooperation and shared roles in reproduction and territoriality, rufous horneros likely represent other Neotropical ovenbirds (Furnariidae). Therefore, further research into the adaptive trade-offs of prolonged pair bonds in rufous horneros could shed light on the evolution of perennial monogamy in birds.
Sempre juntos: um vínculo de par extremamente duradouro em joões-de-barro
Keywords: Divorce; Furnariidae; Furnarius rufus; Monogamy; Pair bond; Prolonged pair bond